(untitled) (Journal of Partial Differential Equations, 2020)
The initial boundary value problems (IBVP) for the P-system with damping on [0, 1] × (0, +∞) arc considered. The global existence of smooth solutions for the TBVP are proved, and their large-time behavior is analyzed. The time-asymptotic equivalence of these solutions to the solutions of the IBVP for the reduced system (1.2) is shown.